Equipping student teachers for the future - Karmen Johansson; Cecilia Nihlén (European Teacher Education Network, 2018)
This paper discusses internationalisation through field studies abroad organized within English courses for student teachers at the University of Gothenburg, Sweden. A pilot study sheds light on similarities and differences encountered concerning the school systems. The overall aims of the study were to investigate the learning outcomes and the development of global teaching skills. The results indicate a high level of satisfaction among the students regarding the experience of recognizing similarities between their own Swedish school system and the English one, in particular the insight and inspiration gained from the differences. Hence, this pilot study provides support for future regular and effective cooperation between different European universities regarding the development of student teachers' global teaching skills.